Indeks Kenyamanan Berdasarkan Kondisi Iklim Mikro dan Persepsi Pengunjung di Bukit Pelangi, Kota Sangatta: Comfort Index Based on Microclimate Conditions and Visitor Perceptions in Bukit Pelangi, Sangatta City - Gunawan, Sahrul; Karyati, Karyati; Sarminah, Sri; Karmini (PERENNIAL, 2026)
Bukit Pelangi is one of the areas that has urban green open spaces in Sangatta City. Venus Park, which is located in the Bukit Pelangi area, has many functions, including absorbing carbon dioxide (CO₂), producing oxygen (O₂), lowering the environmental temperature, and providing a cool atmosphere, making it a choice place to relax.This study aims to determine the microclimate conditions and the level of comfort in three different land cover types (Venus Park, built-up areas, and open land) as well as to understand visitor perceptions of the comfort and available facilities in Venus Park, Sangatta City. Data collection was conducted using an environment meter for 30 days, measuring indicators such as light intensity, air temperature, air humidity, and visitor perceptions through questionnaires. The results showed that the average light intensity in Venus Park was 897.2 lux, in built-up areas 1,690.5 lux, and in open land 2,006.9 lux. The average air temperature in Venus Park was 28.1°C, in built-up areas 29.3°C, and in open land 29.9°C. The average air humidity in Venus Park was 81.1%, in built-up areas 76.2%, and in open land 75.2%. The comfort index (Temperature Humidity Index) for Venus Park (27.3), built-up areas (27.9), and open land (28.4) are included in the comfortable category. Based on visitor perceptions, the level of comfort in Venus Park was categorized as good. The information about comfort index and visitor perception can be used as a reference in planning the development of green open spaces, such as city parks, urban forests, and other open areas.